PERANAN MODAL SOSIAL DALAM KEMENANGAN SATONO DARI JALUR INDEPENDEN PADA PEMILIHAN UMUM KEPALA DAERAH DI KABUPATEN LAMPUNG TIMUR TAHUN 2010 - I Gede Parguna Wisesa; Budi Setiyono; Susilo Utomo (Journal of Politic and Government Studies, 2014)
AbstractThis study analyzes the phenomenon of regional head candidates win elected throughindependent pathways in the election of regional heads in East Lampung District in the year2010, kadidat winner is elected to partner Satono-erwin that in fact they are a couple thatcarried through the non-party or often we call independent in the general election in 2010 alone,in Lampung, as many as 10 districts / cities in sequence hold pilbup / pilwali. The elections in2010 opened new opportunities for players who prefer to use an independent candidate when theimpenetrable political party lines as most political parties already have a candidate. What is thechance that an individual candidate or more popularly called